Transformative Peace Pedagogy: Fostering a Reflective, Critical, and Inclusive Praxis for Peace Studies (In Factis Pax: Journal of Peace Education and Social Justice, 2016)
One of the key conclusions of a 2014 conference on “Reconstructing Peace Studies,” was that how we teach is as important as what we teach. Faculty participating in the conference agreed they had minimal knowledge or preparation in the methods andpedagogies of peace education seen as essential to pursuing the transformative outcomes of peace studies programs. This article offers a brief philosophical and pedagogical framework and rationale for transformative peace pedagogy as a preferred approach and philosophy of teaching and learning in peace studies. Transformative peace pedagogyfosters the development of  a self-reflective praxis and nurtures a holistic, inclusive relationship between the inner (personal) and outer (political, action oriented) dimensions of peacebuilding. This praxis is the basis for both internal consideration and social and political action that is pursued by peace studies.